Liquid Medication Dosing Error amongst Parents/ Caregivers at Outpatient Clinic - Patel, Smit; Kolte, Sharvari; Magdalia, Hemal; Bhatt, Sandipkumar; Patel, Rohit (Journal of Pharmacy Practice and Community Medicine)
Objectives: To evaluate the effectiveness of Patient Information Leaflet (PIL) based educational intervention to improve liquid medication measuring ability of parents/ caregivers. Simultaneously, to assess parents’ measuring ability by dosing instrument type, and identify the association of various factors with dosing errors. Materials and Methods: A multi-centric, randomized controlled interventional study conducted at 2 pediatric clinics in Gandhinagar, Gujarat. Primary caregivers who would be giving medication to the patient (1 year to 12 years) were randomized in an alternative manner into control (without education) and intervention group (education with PILs), and asked to measure a dose of 5 mL using 3 measuring devices: dosing cup, oral dropper and calibrated spoon. Measured doses were categorized as an accurate dose (<10% deviation), acceptable dose (10%-20% deviation) and inaccurate dose (>20% deviation). Results: Total 164 parents/caregivers were enrolled and randomized; 82 in each group. Overall, 65.8% and 79.2% measured doses were accurate in the control and intervention group, respectively (p=0.0018). The range of measured doses (mL) of control group was higher than that of intervention group. About the instruments, the maximum number of participants measured an inaccurate dose with the calibrated spoon (10.9%), and the range of doses of oral dropper and calibrated spoon were higher than that of the dosing cup. Additionally, the likelihood of making dosing errors was not associated with the instruments used, gender, age and education level of the participants. Conclusion: The education provided to the participants helped to improve their measuring ability. Participants’ measuring ability was better while using the dosing cup as compared with the use of oral dropper and calibrated spoon.
Keywords: Pediatric; Oral liquid medication; Parent’s dosing error; Medication error; Patient education